Triptycene molecular rotors mounted on metallofullerene Sc3C2@C80 and their spin–rotation couplings. Issue 38 (21st September 2018) - Meng, Haibing; Zhao, Chong; Nie, Mingzhe; Wang, Chunru; Wang, Taishan
Abstract : Molecular machines have received considerable attention due to their various applications. Abstract : Molecular machines have received considerable attention due to their various applications. Except for mechanical motion, it is essential to design advanced molecular machines with integrated functions. In this study, the triptycene rotor has been covalently linked to paramagnetic metallofullerene Sc3 C2 @C80 with an unpaired electron spin, resulting in a coupled system between spin flip and rotor speed. Two types of triptycene rotors were employed, one is pristine triptycene and another one has a sterically hindered methyl group. Temperature-dependent electron paramagnetic resonance (EPR) spectroscopy revealed that spin-rotor coupling can be modulated by the rotation speed of triptycene rotors, which was further illustrated by variable-temperature 1 H NMR. EPR simulation revealed that the rotations of the attached triptycene rotors can greatly influence the spin relaxation and spin–metal hyperfine couplings of Sc3 C2 @C80, realizing remote control on neighboring electron spin states. These findings of the coupled system between the molecular rotor and spin flip would provide an approach to design advanced molecular machines with magnetic function.